Complete chloroplast genome of Alternanthera philoxeroides by de novo sequencing. Issue 7 (3rd July 2021) - Jiang, Ping; Xu, Guangpei; He, Yanfei; Sun, Taotao; Liu, Changli; Chen, Cunwu; Zuo, Ruihua; Sun, Chuanbo
Abstract: Alternanthera philoxeroides (Mart.) Griseb. ( Alternanthera philoxeroides ) is an important herbage species, which could provide high-quality feed for livestock and poultry breeding. This paper is the first to report the A. philoxeroides's chloroplast genomes, which were detected by de novo sequencing. The results showed that the length of A. philoxeroides' chloroplast genome sequence was 152, 255 bp, including a large single-copy (LSC) region (84, 670 bp), a small single-copy (SSC) region (17, 343 bp), and two inverted repeat (IR) regions (25, 121 bp). Alternanthera philoxeroides' chloroplast genome encoded 132 genes including 8 rRNA, 38 tRNA, and 86 protein-coding genes. After phylogenetic and cluster analysis, A. philoxeroides was closest to Amaranthaceae, and the relationship between Amaranthus and Achyranthes was closest.